Evaluation and Comparison of The Ef-fect of Artificial saliva and Mouthwash Solution on Force Degradation of Different Types of Orthodontic Traction Aids (Comparative in Vitro Study) - Khudair A Al-Jumaili; Abdulrahman I Ali (University of Mosul, College of Dentistry, 2011)
Aims: To determine the amount of force degradation of three types of orthodontic traction aid polyure-thane elastomeric chain (PEC), nickel titanium closed coil spring (NiTi CCS) and stainless steel closed coil spring (SS CCS). Material and methods: Samples were extended to a specific distance which was 18 mm in case of PEC and 20 mm in case of NiTi CCS and SS CCS. Each extended sample will then incubated in dry condition, artificial saliva, and mouthwash solution, for total incubation period of three weeks. Results: showed that samples in dry condition always showed minimum force degrada-tion percent than in wet conditions. It also showed that the increase of incubation time leads to increase in force degradation percent with major degradation percent located within first twenty four hours. Conclusions: in dry and two wet conditions, NiTi CCS reflects the lowest percent of force degradation, PEC showed highest percent, while SS CCS showed intermediate one.